(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the role of digital technologies in teaching hypertension treatment regimens in pharmacology within modern medical education. Arterial hypertension is a widespread chronic disease that requires a comprehensive understanding of complex pharmacotherapeutic approaches, including combination therapy. The study examines the epidemiology, pharmacological characteristics of antihypertensive drugs, and the scientific basis of combination pharmacotherapy. Particular attention is given to the use of digital tools such as multimedia resources, virtual simulations, and interactive platforms in the teaching process. These technologies improve students’ understanding of treatment algorithms, enhance visualization of pharmacological mechanisms, and promote active learning. Furthermore, digital technologies contribute to the development of clinical reasoning and decision-making skills through simulated clinical scenarios. The findings indicate that the integration of digital technologies significantly improves learning outcomes, increases student motivation, and enhances the overall quality of pharmacology education.